Laminin-5 and insulin-like growth factor-II mRNA binding protein-3 (IMP3) expression in preoperative biopsy specimens from oral cancer patients: Their role in neural spread risk and survival stratification. Issue 12 (December 2016) - Tarsitano, Achille; Asioli, Sofia; Morandi, Luca; Monti, Valentina; Righi, Alberto; Morselli Labate, Antonio Maria; Nardi, Elena; Foschini, Maria Pia; Marchetti, Claudio
Abstract: Perineural invasion (PNI) hinders the ability to establish local control of oral squamous cell carcinoma (OSCC). To date, PNI can be evaluated only in surgical specimens and not in preoperative biopsy material, rendering timely therapeutic planning impossible. Insulin-like growth factor-II mRNA binding protein-3 (IMP3) expression appears to be of diagnostic and prognostic utility for many solid tumours, and laminin-5 expression in surgical specimens has been identified as a valid predictor of neural spread of head-and-neck neoplasms. The ability to use preoperative biopsy material to identify patients exhibiting PNI is fundamental for good management of OSCC. We examined a series of 64 consecutive patients treated (primarily via surgery) for OSCC between 2009 and 2014 at the Maxillofacial Surgery Unit, University of Bologna. We evaluated IMP3 and laminin-5 expression in preoperative biopsy material using immunohistochemistry and quantitative reverse transcription polymerase chain reaction. We sought to correlate expression of IMP3 and laminin-5 with PNI evident in surgical specimens. Expression of IMP3 and laminin-5 in preoperative biopsy material appeared to be predictive of PNI in patients with OSCC (P < 0.001). Additionally, the results of multivariate analyses showed that IMP3 status was an independent predictor of death of patients with OSCC (P = 0.001). The present study demonstrates that IMP3 and laminin-5 expression in preoperative biopsy material correlate well with PNI status and may allow accurate preoperative risk stratification of patients with OSCC.